Answer:
(3, -5)
Explanation:
We will use the method of substitution to solve this.
We replace the 2nd equation in the first equation to get an equation in "x" only and use algebra to solve for x first. Shown below:
![x+3y=-12\\x+3((1)/(3)x-6)=-12\\x+x-18=-12\\2x=-12+18\\2x=6\\x=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2azx0ouj8irhgiggwmcfw0j68xpn5a039p.png)
The value of x is 3.
Now, we substitute x = 3 into 2nd equation to get value of y:
![y = (1)/(3)x - 6\\y = (1)/(3)(3) - 6\\y = 1-6\\y=-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d7mzwsp87novf4mq0mgmy9fzc7ogx0e2ld.png)
The value of y is -5
So, the coordinate pair solution is:
(x, y)
(3, -5)